Peningkatan Kompetensi Guru Dalam Persiapan dan Proses Pembelajaran Melalui Workshop Dan Supervisi Edukatif Kolaboratif di SMP N 30 Sijunjung - Evitrah (Warta Pendidikan | e-Journal, 2020)
Through the supervision program of the principal for teachers who have obstacles for preparation and conducting the learning proces, it was expected that they were able to overcome the problems in the implementation of the 2013 curriculum. So that the teachers understand and able to implement the 2013 curriculum well in preparing and conducting the teaching and learning activities This research was carried out at SMP N 30 Sijunjung in 201802019 and 2019/2020 school year, because the school is assisted by researcher or researcher as principal at this school. Supervision is carried out such as holding a short workshop on understanding and implementing the 2013 curriculum and carrying out collaborative educational supervision periodically by emphasizing the provision of assistance to improve learning processes. The data collected was analyzed using quantitative analysis. From the school action research that has been done it can be seen that (1) The results of the academic supervision on preparations of learning proces have increased, both from initial observations with an average value of 84.29 in the first cycle increasing to 88.57 and at the second cycle could reach 94.29, then (2) The results of academic supervision of the conducting of learning have increased, both from initial observations with an average value of 85.63 in the first cycle increased to 87.28 and implementation in the second cycle could reach 91.90.